Match Zehnder interferometry and Laguerre–Gaussian fields dependent photon drag in atomic medium. (1st April 2023) - Muhammad, Nisar; Arif, Syed Muhammad; Bacha, Bakht Amin; Javed, Muhammad; Khan, Aurangzeb
Abstract: The absorption, dispersion and transmission are controlled and modified with the intensities of Laguerre–Gaussian control fields in a four level cesium atomic medium. The normal and anomalous slope of dispersion are investigated for subluminal and superluminal propagation. The maximum measured value of positive/negative group index is n g =±1×10 7, at which, the group velocity is ±30 ms −1 . The maximum delay time between the two beams at the detector without dragging is 0.414 ns and in the presence of dragging is measured to 0.44 ns. The fractional change in delay time without and in the presence of dragging Δ t F is measured to ±2%. The maximum phase shift without dragging is reported to 2.6 micro radian and in the presence of dragging is investigated to ±4 micro radian. The fractional change in phase shift is reported from −200% to 50% and may be used for gravitational waves detection and other signals identification.